1994
DOI: 10.1111/j.1528-1157.1994.tb02446.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double‐Blind, Placebo‐Controlled, Clinical Trial of D‐α‐Tocopherol (Vitamin E) as Add‐on Therapy in Uncontrolled Epilepsy

Abstract: In a double-blind, cross-over trial, vitamin E, and placebo were compared as add-on therapy in 43 patients with uncontrolled epilepsy. The study consisted of a 3-month baseline period followed by two treatment phases of vitamin E or placebo with cross-over to the second phase after 3 months. No significant side effects were noted during the study. Mean seizure frequency in the baseline period was 15.9 +/- 10.5 as compared with 11.8 +/- 10.9 during the placebo phase and 13.7 +/- 11.1 during the vitamin E phase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…On the other hand, clinical trials have yielded conflicting results for the effect of α-tocopherol as an adjunctive antiepileptic agent. Ogunmekan and Hwang (1989) reported that α-tocopherol supplementation significantly reduced seizures; however, Raju et al (1994) did not show any significant difference between α-tocopherol and placebo. Although both trials were done in refractory epileptic patients, Ogunmekan and Hwang (1989) enrolled child patients, whereas Raju et al (1994) enrolled adult patients.…”
Section: Antioxidant Strategy For Seizurementioning
confidence: 91%
See 2 more Smart Citations
“…On the other hand, clinical trials have yielded conflicting results for the effect of α-tocopherol as an adjunctive antiepileptic agent. Ogunmekan and Hwang (1989) reported that α-tocopherol supplementation significantly reduced seizures; however, Raju et al (1994) did not show any significant difference between α-tocopherol and placebo. Although both trials were done in refractory epileptic patients, Ogunmekan and Hwang (1989) enrolled child patients, whereas Raju et al (1994) enrolled adult patients.…”
Section: Antioxidant Strategy For Seizurementioning
confidence: 91%
“…Ogunmekan and Hwang (1989) reported that α-tocopherol supplementation significantly reduced seizures; however, Raju et al (1994) did not show any significant difference between α-tocopherol and placebo. Although both trials were done in refractory epileptic patients, Ogunmekan and Hwang (1989) enrolled child patients, whereas Raju et al (1994) enrolled adult patients. Moreover, the duration of α-tocopherol supplementation was limited to 3 months (Raju et al, 1994), which may be too short for precise evaluation of the effect of α-tocopherol.…”
Section: Antioxidant Strategy For Seizurementioning
confidence: 91%
See 1 more Smart Citation
“…2007;Joshi et al, 1999;Peled et al, 2001;Peterson et al, 1976;Pfeiffer and LaMola. 1983;Raju et al, 1994;Sullivan et al, 1990;Tamai et al, 1988;Gaby, 2007;Torres et al, 1999;Trimble et al, 1980;Turner et al, 1977). Several different nutrients (and two hormones) may also be beneficial in selected patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…It delayed the onset of seizures in the intracerebral ferrous chloride model, but not in the animal models commonly used to screen for anticonvulsant drug actions. However, a double‐blind placebo‐controlled, cross‐over trial (Raju et al, 1994) with vitamin E as add‐on therapy in 43 patients with uncontrolled epilepsy demonstrated no efficacy with regard to seizure control.…”
Section: Vitamins and Other Nutrients In Patients With Epilepsy (Tablmentioning
confidence: 99%